The construction of an otter door. - Mariñas, Pedro S. (College of Fisheries, University of the Philippines, 1951)
Six months had past that every student had to undergo practical training and as required by Philippine institute of fisheries technology in order to complete the requirements for graduation. As a member of this institution, I tried my best to secured it with the recommendation by fellow graduate. This firm is presently located at Damortis, Sto. Tomas, La Union. Two fellow graduates run this from this institution with the aid of the bureau, by leasing one of the government own boat. This boat was formerly a tugboat but was converted into a trawling vessel. Concerning the final report, which we are supposed to perform, I was assigned to make a report on how to construct an otter door. This part o the gear is the most important during the operation, which makes the trawl function. In these part of the gear it is not easy to construct because once you are wrong in its computation especially in the chains, the door will not properly function and besides there will be no catch or none at all. So, in the construction of the otter door, be sure that all parts are properly computed in order to gain a successful operation. Its just only a matter of computation.